Expression of Mitochondrial Cytochrome C Oxidase Chaperone Gene (COX20) Improves Tolerance to Weak Acid and Oxidative Stress during Yeast Fermentation. - Vinod Kumar; Andrew J Hart; Ethiraju R Keerthiraju; Paul R Waldron; Gregory A Tucker; Darren Greetham (PLoS ONE)
Introduction Saccharomyces cerevisiae is the micro-organism of choice for the conversion of fermentable sugars released by the pre-treatment of lignocellulosic material into bioethanol. Pre-treatment of lignocellulosic material releases acetic acid and previous work identified a cytochrome oxidase chaperone gene (COX20) which was significantly up-regulated in yeast cells in the presence of acetic acid. Results A Δcox20 strain was sensitive to the presence of acetic acid compared with the background strain. Overexpressing COX20 using a tetracycline-regulatable expression vector system in a Δcox20 strain, resulted in tolerance to the presence of acetic acid and tolerance could be ablated with addition of tetracycline. Assays also revealed that overexpression improved tolerance to the presence of hydrogen peroxide-induced oxidative stress. Conclusion This is a study which has utilised tetracycline-regulated protein expression in a fermentation system, which was characterised by improved (or enhanced) tolerance to acetic acid and oxidative stress.